PERKEMBANGAN TANAH DARI LAPUKAN BATUAN ULTRABASA PADA DUA TOPOSEKUEN DI SULAWESI TENGGARA - Sunarminto, Bambang Hendro; Siradz, Syamsul Arifin (Jurnal Agroteknos, 2011)
The study of soil development of weathering ultramafic rocks have been performed on several toposequence in Sulawesi Tenggara in Puriala Subdistrict of Konawe District and in Lasusua Subdistrict of Kolaka District from December 2010 until Juni 2011. The results showed that soils developed from ultramafic rocks weathering low rainfall (torric) in Puriala have a more coarse texture (LS, SL, L, SiL, CL, C), impervious container which was more shallow (20-90 cm), land of color tend to be brown (7.5 YR), pH 6.8 to 7.6, C-organic 0.57 to 0.93%, CEC 26.20 to 69.61 cmol(+)kg-1, the number of base 11.90 to 15.86 cmol(+)kg1, Fe-d 3.79 to 16.12%, Al-d 0.14 to 1.65%, smectite clay minerals, sand mineral feldspar hematite compared soils developed from ultramafic rocks weathering high rainfall (udic) in Lasusua color tends to be more red (2.5 YR), with a finer texture (SiCL, C) and impervious container deeper (70 -> 150 cm), pH 6.1 to 7.0, C-organic 1.20 to 1.86%, CEC 11.29 to 31.60 cmol(+)kg-1, the number of bases 2.72 to 13.33 cmol(+)kg-1, Fe-d 21.62 to 27.04%, Al-d 0.87 to 3.58%, gutit smectite clay minerals, sand mineral feldspar-magnetite-hematite. Soil weathering from ultramafic rocks with high rainfall experienced base cations leaching was higher mainly characterized by high mobility of cations with CEC and a lower base amount, and the accumulation of low mobility of cations is characterized by high Fe-d and Al-d. Level of soil development began from P2 (Entisol), P1 (Vertisol), L2 (Inceptisol), P3 (Inceptisol), L1 (Alfisol) and the last L3 (Oxisol) the most advanced of soil is on the middle slope, the next is soil on summit, and the last is soil on toeslopes